2017
DOI: 10.29252/jafm.73.245.27351
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Mass Transfer Enhancement in Absorption of Vapor in Laminar Liquid Film by Adding Nano-Particles

Abstract: In this paper, a numerical study was performed. The effect of nanoparticles on the absorption of vapor into a liquid film of lithium bromide aqueous solution flowing down over a cooled vertical channel is examined. The present model uses the numerical finite volume method to solve the parabolic governing equations for twodimensional and laminar flow. In this model, the cooling water flows countercurrent to a solution of concentrated lithium bromide mixed with the nanoparticles. The water vapor is then absorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The liquid-mixture interface is in thermodynamic equilibrium. The axial diffusion of heat, mass and momentum are negligible (Feddaoui et al (2001)); that the heat transfer by the radiation, Soret and Dufour effects are negligible (Armou et al (2017)). Finally, the gas and the liquid phases have the same pressure.…”
Section: Fig 1 Model Domainmentioning
confidence: 99%
“…The liquid-mixture interface is in thermodynamic equilibrium. The axial diffusion of heat, mass and momentum are negligible (Feddaoui et al (2001)); that the heat transfer by the radiation, Soret and Dufour effects are negligible (Armou et al (2017)). Finally, the gas and the liquid phases have the same pressure.…”
Section: Fig 1 Model Domainmentioning
confidence: 99%
“…Some scholars have discussed the influence of nanoparticles on the performance of the absorber by numerical simulation. Armou et al [11] established a CFD model for falling film absorption of nanofluids in laminar flow based on the assumption that the wall temperature changes linearly. The numerical results revealed that nanofluids have higher mass transfer capacity.…”
mentioning
confidence: 99%